Impact of Oral Submucous Fibrosis on Quality of Life - Babar Aman, Nausheen Jawaid, Awais Akbar, Kiran Akram, Aatif Mohammad Haroon, Yusra Roohi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral submucous fibrosis (OSMF) is a chronic, insidious, potentially malignant condition primarily affecting populations with areca nut chewing habits. It significantly impairs oral functions and is associated with restricted mouth opening, burning sensations, and altered speech and eating, which can severely impact a patient’s quality of life (QoL). Aim: To assess the impact of OSMF on the quality of life in patients attending a tertiary care hospital using the WHOQOL-BREF questionnaire. Methodology: This was a cross-sectional observational study conducted at the Department of Maxillofacial Surgery, Abbasi Shaheed Hospital Karachi from 5th September 2022 to 4th March 2023. A total of 120 patients diagnosed with OSMF were enrolled. Demographic data and clinical features were recorded, and QoL was assessed across four domains - physical health, psychological health, social relationships, and environmental health - using the WHOQOL-BREF questionnaire. Results: Majority of patients were male (65%), with a mean age of 44.7 years. The most affected domains were psychological and social relationship domains. Only 3 patients (2.5%) reported very poor QoL, while 49 patients (40.8%) reported good QoL. Stratification revealed significant associations between QoL and age, gender, residential status, BMI, and educational level. Conclusion: Oral submucous fibrosis has a variable impact on quality of life, with some patients experiencing substantial impairment. Early diagnosis, patient counseling, and multidisciplinary management are crucial for improving outcomes. Keywords: Oral submucous fibrosis (OSMF), Quality of life, WHOQOL-BREF, Oral health, Potentially malignant disorder